4q-6n3m=f

Multiply both sides of the equation by 3m.

4q-6n=f⋅(3m)

Remove parentheses.

4q-6n=f⋅(3m)

Rewrite using the commutative property of multiplication.

4q-6n=3fm

Add 6n to both sides of the equation.

4q=3fm+6n

Divide each term in 4q=3fm+6n by 4.

4q4=3fm4+6n4

Cancel the common factor of 4.

Cancel the common factor.

4q4=3fm4+6n4

Divide q by 1.

q=3fm4+6n4

q=3fm4+6n4

Cancel the common factor of 6 and 4.

Factor 2 out of 6n.

q=3fm4+2(3n)4

Cancel the common factors.

Factor 2 out of 4.

q=3fm4+2(3n)2(2)

Cancel the common factor.

q=3fm4+2(3n)2⋅2

Rewrite the expression.

q=3fm4+3n2

q=3fm4+3n2

q=3fm4+3n2

q=3fm4+3n2

Solve for q (4q-6n)/(3m)=f